One human settlement: A transdisciplinary approach to climate change adaptation research. (January 2015) - Serrao-Neumann, S.; Schuch, G.; Harman, B.; Crick, F.; Sano, M.; Sahin, O.; van Staden, R.; Baum, S.; Low Choy, D.
Highlights: Transdisciplinary research approaches are conducive to climate change adaptation. Integration of research outputs maybe achieved through a unified theme. A selected sector can be used as a platform to (re)integrate and apply created knowledge. Abstract: The threat of climate change demands that human settlements adapt to unavoidable impacts. Climate change is a complex problem that requires traditional disciplines to work together to facilitate an integrated and coordinated response to its impacts. Transdisciplinary research approaches have been recognised for being well placed to aid responses to complex problems such as climate change. This paper draws on the experience of the South East Queensland Climate Adaptation Research Initiative (SEQCARI), Australia, to reflect upon the challenges involved in undertaking transdisciplinary research aimed at developing and improving a range of adaptation options for specific sectors as well as across sectors. Challenges and learning's are discussed based on the three phases of transdisciplinary research processes: problem framing and team building, co-creation of solution-oriented transferable knowledge, and (re)integration and application of created knowledge. Four key insights are then discussed to advance transdisciplinary research approaches for climate change adaptation: adoption of a dynamic learning approach such as learning-by-doing/doing-by-learning to provide sufficient flexibility and scope to navigate potential barriers and conflicts; selection of social sciences to drive integration; choice of one sector as a platform for integration; and acknowledgement of existing barriers and limitations associated with the political context in which the research takes place.